Systematic review of the prevalence, symptomatology and management options of sexual dysfunction in women with multiple sclerosis. Issue 1 (25th November 2019) - Polat Dunya, Cansu; Tulek, Zeliha; Uchiyama, Tomoyuki; Haslam, Collette; Panicker, Jalesh N.
Abstract: Aims: Sexual dysfunction (SD) is highly prevalent in women with multiple sclerosis (MS), however little is known about treatment options. The aim of this paper is to review the prevalence, symptomatology, and management options of sexual dysfunction in women with MS. Methods: The Cochrane Database of Systematic Reviews, MEDLINE, EMBASE, CINAHL, AMED, PsycINFO, PEDro, Database of International Rehabilitation Research, Occupational Therapy Systematic Evaluation of Evidence, ClinicalTrials.gov, and Current Controlled Trials databases were searched. No limitations were placed on the date. A critical appraisal of the literature on SD in women with MS was performed according to the PRISMA statement. Two reviewers screened and extracted data. Study quality was evaluated using a standardized tool. Results: A search of 12 databases identified 61 relevant studies (33 observational, 14 case‐control, 4 follow up, 10 interventional). Significant variability in the prevalence of SD and questionnaires used to evaluate SD were observed. The most commonly reported sexual difficulties were problems with desire, arousal, and orgasm. Different demographics and MS‐related characteristics were found to contribute to SD. Few studies have evaluated interventions for treating SD, and bias was high because of the weak quality of trial designs. Conclusions: SD in women with MS is multidimensional, comparable in prevalence with other neurological disorders and increases with advancing disease. Studies evaluating practical strategies and pharmacological interventions are few, and properly designed trials using MS‐specific validated outcome measures of SD are required to inform evidence‐based treatment options for this high impact MS‐related dysfunction.